2008
DOI: 10.1080/15563650802178136
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid poisoning: An evidence-based consensus guideline for out-of-hospital management

Abstract: A review of US poison center data for 2004 showed over 9000 ingestions of valproic acid. A guideline that determines the conditions for emergency department referral and prehospital care could potentially optimize patient outcome, avoid unnecessary emergency department visits, reduce health care costs, and reduce life disruption for patients and caregivers. An evidence-based expert consensus process was used to create the guideline. Relevant articles were abstracted by a trained physician researcher. The first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 59 publications
0
31
1
1
Order By: Relevance
“…The present study demonstrated the various efficiencies of three different approaches to experimental ablation of VPA ER in rats. Oral administration of charcoal has been reported to eliminate more than half of the ER-related absorption of VPA in humans (Neuvonen et al, 1983), and administration of activated charcoal can be used to treat acute VPA overdose (Manoguerra et al, 2008). However, activated charcoal did not impact VPA ER in this study.…”
Section: Discussioncontrasting
confidence: 49%
“…The present study demonstrated the various efficiencies of three different approaches to experimental ablation of VPA ER in rats. Oral administration of charcoal has been reported to eliminate more than half of the ER-related absorption of VPA in humans (Neuvonen et al, 1983), and administration of activated charcoal can be used to treat acute VPA overdose (Manoguerra et al, 2008). However, activated charcoal did not impact VPA ER in this study.…”
Section: Discussioncontrasting
confidence: 49%
“…For more than 4 decades VPA stipulate in clinical practice as an anticonvulsant to control seizures in forms of tonic-clonic (grand mal), complex partial and juvenile myoclonic. Published report by International League Against Epilepsy (ILAE) authorizes the efficiency and value of ethosuximide and VPA for children with absence seizures as initial monotherapy [2][3][4][5][6][7][8][9][10][11][12]. Karlov et al [11] reported a prescription based on valproate in dose 15 -25 mg/kg/day and levetiracetam in dose 20 -25 mg/kg/day that were used in the treatment of 23 patients with juvenile myoclonic, juvenile absence, and convulsive idiopathic generalized and children absence epilepsy.…”
Section: Resultsmentioning
confidence: 99%
“…For the treatment of absence epilepsy, it seems that older AEDs such as ethosuximide and VPA are more efficacious than newer AEDs. Due to reduced side effects, ethosuximide remains the first line treatment for childhood absence epilepsy [2][3][4].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations